Precision doublet of magnetic quadrupole lenses for ion beam formation - Ponomarev, A.G.; Rebrov, V.A.; Kolinko, S.V.; Salivon, V.F. (Вопросы атомной науки и техники, 2020)
The precision doublet of magnetic quadrupole lenses is presented. The doublet yoke and poles made from a single piece of soft magnetic iron. Doublet manufacturing technology provides of alignment of the geometric axes in the lenses with an accuracy of a few microns. The doublet geometry was chosen to obtain the maximum magnetic induction at the poles for a given radius of the lens aperture as a result of numerical simulation. An experimental study of the doublet properties was carried out using a setup for field reconstruction technique for magnetic quadrupole lenses. The relative position of the physical axes of the lenses (the geometrical location of points with zero magnetic induction) and the magnitudes of the parasitic multipole field components were determined. Розглянуто прецизійний дублет магнітних квадрупольних лінз. Ярмо і полюса дублета виготовлені з цілісного шматка магнітом’якого заліза. Технологія виготовлення дублета забезпечує співвісність геометричних осей в лінзах з точністю до декількох мікрометрів. Геометрія дублета була обрана з метою отримання максимальної магнітної індукції на полюсах для заданого радіуса апертури лінзи в результаті чисельного моделювання. Експериментальне дослідження властивостей дублета проводилося на установці для відновлення поля в магнітних квадрупольних лінзах. Визначено відносне положення фізичних осей лінз (геометричне розташування точок з нульовою магнітною індукцією) і величини паразитних мультипольних компонент поля. Рассмотрен прецизионный дублет магнитных квадрупольных линз. Ярмо и полюса дублета изготовлены из цельного куска магнитомягкого железа. Технология изготовления дублета обеспечивает соосность геометрических осей в линзах с точностью до нескольких микрометров. Геометрия дублета была выбрана с целью получения максимальной магнитной индукции на полюсах для заданного радиуса апертуры линзы в результате численного моделирования. Экспериментальное исследование свойств дублета проводилось на установке для восстановления поля в магнитных квадрупольных линзах. Определены относительное положение физических осей линз (геометрическое расположение точек с нулевой магнитной индукцией) и величины паразитных мультипольных компонент поля.